2017
DOI: 10.7189/jogh.07.010411
|View full text |Cite
|
Sign up to set email alerts
|

Solar powered oxygen systems in remote health centers in Papua New Guinea: a large scale implementation effectiveness trial

Abstract: BackgroundPneumonia is the largest cause of child deaths in Papua New Guinea (PNG), and hypoxaemia is the major complication causing death in childhood pneumonia, and hypoxaemia is a major factor in deaths from many other common conditions, including bronchiolitis, asthma, sepsis, malaria, trauma, perinatal problems, and obstetric emergencies. A reliable source of oxygen therapy can reduce mortality from pneumonia by up to 35%. However, in low and middle income countries throughout the world, improved oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…We will test this hypothesis in a stepped-wedge clusterrandomized study in Uganda. SPO 2 has a number of benefits that lend themselves to further scale-up: reliability in settings with poor access to electricity or O 2 cylinders [31]; abundance of solar radiation in target LMICs in the tropics [32]; minimal maintenance and training requirements [32]; and cost- Fig. 4 Computer simulation for sample size estimation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will test this hypothesis in a stepped-wedge clusterrandomized study in Uganda. SPO 2 has a number of benefits that lend themselves to further scale-up: reliability in settings with poor access to electricity or O 2 cylinders [31]; abundance of solar radiation in target LMICs in the tropics [32]; minimal maintenance and training requirements [32]; and cost- Fig. 4 Computer simulation for sample size estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study sample size was calculated via a computer simulation using real-world parameters using the Uganda DHIS [22,35], data from previous large-scale studies [31], and systematic reviews [22]. We applied our planned primary analysis to the simulated data for > 5000 trials to estimate a required sample size of 2400 patients from 20 sites, with 20 steps, recruited over two years to detect a mortality benefit estimated at 35% with 80% power (α = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…As an additional point, the provision of oxygen has been described as an ‘entry point’ for improving quality of care in lower-middle income countries [ 57 ] and is a vital component of sepsis management [ 4 ]. However, availability is extremely limited in sub-Saharan Africa [ 11 , 13 , 58 , 59 ]: one study identified that only 44% of surveyed facilities (12 countries) had an uninterrupted supply of oxygen [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Installation and maintenance of these ‘oxygen systems’, however, remain a challenge in many health facilities in African countries 13. The combination of solar-powered energy systems and the use of oxygen concentrators can be an option to improve oxygen supply in health facilities in remote settings 14…”
Section: Introductionmentioning
confidence: 99%